Industry 4.0 technologies and firm performance with digital supply chain platforms and supply chain capabilities - Khan Saif-Ur-Rehman; Nora Barson; Yacoub Haider Hamdan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
We used a dynamic resource-based view (DRBV) to examine how Industry 4.0 technologies (I4.0) affect business performance. We also examined whether the relationship between I4.0 and firm performance is sequentially mediated via digital supply chain platforms and supply chain capabilities. We used the PLS-SEM technique to analyze the data. After analyzing data collected from 348 logistics and supply chain managers, we found that adopting I4.0 leads to improved operational performance and digital supply chain platforms (DSCPs). However, I4.0 does not enhance competitive firm performance. DSCPs boost operational and competitive firm performance. Further, supply chain capabilities also boost operational and competitive firm performance. In mediation analyses, DSCPs partially mediate the I4.0 and operational performance relationship. Sequential mediation analyses demonstrate that the I4.0 impact on operational and competitive firm performance is mediated via digital supply chain platforms and supply chain capabilities. Lastly, operational performance boosts competitive performance. The firms should focus on digital supply chain platforms and capabilities, as mere adoption of I4.0 does not lead to competitive performance in the GCC context. The findings of this study have theoretical and practical implications.
Keywords: 330; industry 4.0 technologies; digital supply chain platforms; supply chaincapabilities; operational performance; competitive performance; supply chainmanagement; Gulf Cooperation Council economies